Validating EFL Students’ Evaluations of a Compulsory Matriculation Program: Links to Motivation in an Indonesian Context - Widiatmoko, Paulus (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2025)
Effective management of language programs involves multifaceted components, particularly regarding quality assurance. However, evaluations by program management often overlook student perspectives due to biases, perceived insignificance, or a tendency to view such assessments as routine. This study aimed to investigate students’ quality assessments of a compulsory English matriculation program in an Indonesian private university. A questionnaire, adapted from Student Evaluation of Educational Quality (SEEQ), was distributed to 390 students across eight departments. Descriptive analysis revealed that while students provided predominantly favourable evaluations across all assessed aspects, dimensions of assessment clarity, task relevance, and classroom interactions received comparatively lower ratings. Confirmatory Factor Analysis demonstrated the instrument's validity and reliability, along with its overall good fit measures. Lastly, Pearson Correlation Analysis indicated positive and significant correlations between students' perceived quality of the program and their motivation, with the strongest one on their self-determination. By promoting an environment that prioritizes quality assurance through student evaluations and feedback, educational institutions can stimulate increased student motivation and improve overall outcomes in language acquisition.